VARIAÇÃO LINGUÍSTICA NA SALA DE AULA - Deus, Regiene Arcanjo (WEB REVISTA SOCIODIALETO, 2018)
O presente trabalho foi realizado com alunos do 9°ano do ensino fundamental, através de questionário, buscado conhecer como é realizado o estudo da variação linguística na sala de aula, tendo como aporte teórico a Sociolinguística. Diante dos questionamentos foi identificado que os alunos não têm claro o conceito de variação linguística, eles chegam à escola com conceitos estigmatizados, não considerando a fala que traz do ambiente familiar como sendo parte da Língua Portuguesa. ABSTRACT: The present work was carried out with students of the 9th grade of elementary school, through a questionnaire, seeking to know how the study of linguistic variation in the classroom is carried out, with theoretical contribution to Sociolinguistics. Before the questioning was identified that the students are not clear the concept of linguistic variation, they arrive at the school with stigmatized concepts, not considering the speech that brings of the familiar environment as being part of the Portuguese Language. KEYWORDS: Linguistic Variation, School, Portuguese Language.